The Penguin anthology of twentieth-century American poetry - Dove, Rita (New York Penguin Books, 2011)
An anthology of twentieth-century American poetry, featuring Wallace Stevens, T.S. Eliot, Elizabeth Bishop, Robert Hayden, Gwendolyn Brooks, Derek Walcott, Adrienne Rich, John Ashbery, Anne Sexton, and many others.
Includes index.
Keywords: American poetry -- 20th century